2012
DOI: 10.3892/or.2012.1834
|View full text |Cite
|
Sign up to set email alerts
|

Water extract of Hedyotis Diffusa Willd suppresses proliferation of human HepG2 cells and potentiates the anticancer efficacy of low-dose 5-fluorouracil by inhibiting the CDK2-E2F1 pathway

Abstract: Hedyotis Diffusa Willd (HDW), a Chinese herbal medicine, has been widely used as an adjuvant therapy against various cancers, including hepatocellular carcinoma (HCC). However, the underlying anticancer mechanisms are yet to be elucidated. In the present study, the anticancer effects of HDW were evaluated and the efficacy and safety of HDW combined with low-dose 5-fluorouracil (5-FU) were investigated. HepG2 cells were cultured in vitro and nude mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…Similarly we found water extract of HWD can arrest the HepG2 cells in G0/G1 phase via downregulating the mRNA and protein levels of CDK2, CDK4 and E2F (10). Matrine, a component rich in SF, inhibited cell proliferation through arresting cells in G0/G1 phase in gallbladder cancer cells (31), prostate cancer cells (32) and hepatoma cells (33).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similarly we found water extract of HWD can arrest the HepG2 cells in G0/G1 phase via downregulating the mRNA and protein levels of CDK2, CDK4 and E2F (10). Matrine, a component rich in SF, inhibited cell proliferation through arresting cells in G0/G1 phase in gallbladder cancer cells (31), prostate cancer cells (32) and hepatoma cells (33).…”
Section: Discussionsupporting
confidence: 57%
“…The above herbs may contain ingredients that can inhibit proliferation and promote apoptosis of tumor cells. For example, we found that HDW water extract may inhibit proliferation of cancer cells via regulating the cell cycle (10 Others reported HDW and Prunella may induce cell apoptosis via the mitochondrion-dependent pathway (11)(12)(13)(14). Cell proliferation is controlled by proteins relating to cell cycle in the cytoplasm.…”
Section: Introductionmentioning
confidence: 86%
“…In addition, the extract potentiated the anticancer effect of low-dose 5-FU in the absence of overt toxicity by downregulating the mRNA and protein levels of CDK2, cyclin E and E2F1. [70] MHCC97-H cells Total flavones extract The extract treatment reduced the level of E-cadherin protein and increased the expression of vimentin protein in TGF-β1-induced MHCC97-H. [71] HepG2 cells 1,3-Dihydroxy-2-Methylanthraquinone Ethyl acetate extract Both 1,3-Dihydroxy-2-Methylanthraquinone and ethyl acetate extract exhibited an inhibitory effect on HepG2 cells, resulting in in upregulation of Bax, p53, Fas, FasL, p21 and cytoplasmic cytochrome C levels and caspase-3, -8, -9 proteases activities, while downregulating Bcl-2, mitochondrial cytochrome C, cyclin E and CDK 2 in a dose-dependent manner.…”
Section: Ht-29 Cells Ethanol Extractmentioning
confidence: 99%
“…A number of these natural products were originally used in traditional Chinese medicine and other forms of folk medicine (1).…”
Section: Introductionmentioning
confidence: 99%